SCREENING OF POTATO CULTIVARS AGAINST COMMON SCAB DISEASE IN WEST BENGAL - Basu, A; Maiti, M. K; Chettri, M.; Konar, A (Potato Journal, 2013)
Common scab of potato caused by Streptomyces scabies (Thaxter) Waksman & Henriki is one of the most important diseases of potato and has gradually become a major disease in the plains of West Bengal. Twelve potato cultivars obtained from CPRI, Shimla, were planted in a naturally infested field at Adisaptagram Block Seed Farm, Hooghly, in two successive cropping seasons (2002-2003 and 2003-2004). Out of twelve cultivars, three cultivars (Kufri Lalima, Kufri Sindhuri and Kufri Anand) were least susceptible, three cultivars (Kufri Kanchan, Kufri Badshah and Kufri Giriraj) were medium susceptible, three cultivars (Kufri Pukhraj, Kufri Sutlej and Kufri Jawhar) were highly susceptible and rest three cultivars (Kufri Jyoti, Kufri Chandramukhi and Kufri Ashoka) were very highly susceptible. In general, the red skinned cultivars were least susceptible to the scab pathogen. Besides, cv. Kufri Anand being a white skinned cultivar, was also among the least susceptible. Majority of the hybrids included in this programme were very highly susceptible to the disease. Hence, cultivars found least susceptible in this study may be useful against scab pathogen in breeding programme for this region.